If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (6x + -18y + 27z) + -1(3xyz) = 0 Remove parenthesis around (6x + -18y + 27z) 6x + -18y + 27z + -1(3xyz) = 0 Remove parenthesis around (3xyz) 6x + -18y + 27z + -1 * 3xyz = 0 Multiply -1 * 3 6x + -18y + 27z + -3xyz = 0 Reorder the terms: 6x + -3xyz + -18y + 27z = 0 Solving 6x + -3xyz + -18y + 27z = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '18y' to each side of the equation. 6x + -3xyz + -18y + 18y + 27z = 0 + 18y Combine like terms: -18y + 18y = 0 6x + -3xyz + 0 + 27z = 0 + 18y 6x + -3xyz + 27z = 0 + 18y Remove the zero: 6x + -3xyz + 27z = 18y Add '-27z' to each side of the equation. 6x + -3xyz + 27z + -27z = 18y + -27z Combine like terms: 27z + -27z = 0 6x + -3xyz + 0 = 18y + -27z 6x + -3xyz = 18y + -27z Reorder the terms: 6x + -3xyz + -18y + 27z = 18y + -18y + -27z + 27z Combine like terms: 18y + -18y = 0 6x + -3xyz + -18y + 27z = 0 + -27z + 27z 6x + -3xyz + -18y + 27z = -27z + 27z Combine like terms: -27z + 27z = 0 6x + -3xyz + -18y + 27z = 0 Factor out the Greatest Common Factor (GCF), '3'. 3(2x + -1xyz + -6y + 9z) = 0 Ignore the factor 3.Subproblem 1
Set the factor '(2x + -1xyz + -6y + 9z)' equal to zero and attempt to solve: Simplifying 2x + -1xyz + -6y + 9z = 0 Solving 2x + -1xyz + -6y + 9z = 0 Move all terms containing x to the left, all other terms to the right. Add '6y' to each side of the equation. 2x + -1xyz + -6y + 6y + 9z = 0 + 6y Combine like terms: -6y + 6y = 0 2x + -1xyz + 0 + 9z = 0 + 6y 2x + -1xyz + 9z = 0 + 6y Remove the zero: 2x + -1xyz + 9z = 6y Add '-9z' to each side of the equation. 2x + -1xyz + 9z + -9z = 6y + -9z Combine like terms: 9z + -9z = 0 2x + -1xyz + 0 = 6y + -9z 2x + -1xyz = 6y + -9z The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| 9x^2-4x=-3 | | x-6=5x+14 | | 8.5/x=7/5 | | -x-10=3x+18 | | x/17.5=7 | | -18=-9y | | 2z^2+11z+14=0 | | (X^2)^3x/x^7 | | 6m^2-6m-7=0 | | 5b-45=0 | | 4a=6a+1 | | 7x+9=13x-27 | | n(n-1)=132 | | 1/3v-3/2=-3/5 | | n(n-1)=32 | | y^2-26y+160=0 | | x+44=4x+20 | | C=250+40d | | 4x-14=x+13 | | x-11=4x+16 | | 5-(6+9x)=(4x-1) | | 7.13=2(3.14)r | | 8x+7-3x=5+5x+2 | | 2x-8y-9x+5y= | | -8(-3s-6+8m)= | | X^2-4=45 | | x(x-4)-2=43 | | 77.4(0.681)= | | X+60=35 | | (2+v)(2v+3)=0 | | 3x(12x-5)-6x(6x-5)=0 | | 4x^3-9x^2+7x=2.5 |